Computed tomographic findings in cerebral arterial ectasia. - Goldstein, S J; Sacks, J G; Lee, C; Tibbs, P A; McCready, R A (American Journal of Neuroradiology, 1983)
The computed tomographic findings in 15 patients with angiographically documented cerebral arterial ectasia are reported. In addition to demonstrating the majority of pathologic arterial segments, computed tomography also documents the presence and extent of associated intracranial abnormalities. In this study these included cerebral atrophy (10 patients), infarction (three patients), and subarachnoid hemorrhage (one patient).